Precious And Industrial Metals as A Hedge Against Inflation - Karol WOJTOWICZ (Communications of International Proceedings, 2022)
Investors' interest in commodity markets is primarily driven by the possibility of risk diversification. The low level of correlation of rates of return with classic financial instruments contributed to the increased popularity of commodities assets. Some economists point out that commodity instruments can also limit the negative effects of inflation. Much research on inflation links to assets such as gold and oil, but relatively little study has been devoted to other commodities. The main aim of the article is to verify whether investments in commodity market instruments based on selected metals can be hedged against the negative effects of inflation. Moreover, another objective is to identify possible similarities and differences between particular types of investments. The study results indicate that the commodity futures based on precious and industrial metals were not an effective hedge against inflation. Only in some cases the beta coefficients indicate the potential for protection from price increases, but the high variability in the level of the coefficients implied that the effect was not systematic.
Keywords: commodities; precious and industrial metals; inflation; alternative investments